Vapour Diffusion Open Arctic Wall: A Comparison of Moisture Accumulation Potential Versus Other Cellulose Superinsulation Strategies - Cory Brun (10855527) (2013)
Superinsulation is becoming increasingly attractive in the construction of energy efficient new homes or energy retrofit projects. By increasing the thermal insulation inside walls, new possible unforeseen building durability issues arise that were otherwise not present during standard 2”x6” construction, as there is less potential for drying. The reduced drying is often attributed to using low permeance materials in the building enclosure. One method to combat the reduced drying potential is to use the highest permeable vapour diffusion open materials for all building enclosure components such as the “Arctic Wall”. The purpose of this study is to determine how the Arctic Wall performs in Fairbanks, Alaska in addition to other climates, and how it also compares with other common vapour diffusion open methods. The results of experimental simulation using WUFI 5.2 hygrothermal software have shown that all vapour diffusion open walls have a potential for condensation that is most dominated by the heating load across the climates that were tested. The Arctic Wall was found to be safe to use in all climates using the tested methods, but still poses a potential risk due to potential condensation due to air leakage. The results of this study have shown that the Arctic Wall performed on par with other vapour diffusion open strategies.